PEMISAH AIR DAN CRUDE PALM OIL DENGAN METODE ADSORPSI MENGGUNAKAN SENSOR WARNA TCS3200 DAN SENSOR PHOTODIODE BERBASIS ARDUINO UNO - Muhammad Iqbal Zailany Nasution; Mulkan Iskandar Nasution (Komunikasi Fisika Indonesia, 2023)
To lessen financial damages brought on by industrial mishaps, a device that can recycle or reuse oil emissions mixed with water is required. The purpose of this study was to evaluate the sensor readings for crude palm oil (CPO) oil thickness, presence, and tool effectiveness in separating CPO oil from water. photodiode and the tool's effectiveness in separating the water and oil in CPO. The red frequency value on the TCS3200 color sensor reading increases as the thickness of the oil in the tank increases. The percentage deviation value of the CPO oil volume generated from these results is 9.7%. Before suction or the laser still penetrates the water, the photodiode sensor's light intensity reading is 74, and when it is exposed to oil, the reading is 0. The CPO oil thickness test findings show that as the CPO oil thickness increases, so does the red frequency value on the sensor. The photodiode sensor's laser light reception intensity is 74 when it detects water, and 0 when it detects oil. According to test data, the gadget has a 90.3% success rate in separating water and oil.